PENGARUH POLA KOMUNIKASI ORANG TUA DAN ANAK TERHADAP PEMBENTUKAN PERILAKU ANAK - Nathanael, Garcia Krisnando (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The primary objective of this study is to investigate and analyze communication patterns within families and their influence on the development of children's behavior in the Halim Perdana Kusuma environment. To comprehend how communication dynamics between parents and children impact the shaping of children's behavior, a quantitative approach employing survey questionnaires is utilized. The research reveals that the communication patterns (X1) between parents and children contribute to a 17% impact on the formation of child behavior (Y1). The correlation analysis indicates a correlation coefficient of 0.130 between variables X1 and Y1. The outcome of the simple linear regression demonstrates a positive relationship (0.096) between variable X1 and variable Y1. Furthermore, hypothesis testing utilizing the t-formula on the family communication pattern variable (X1) reveals a t-count of 1.297, which is less than the critical t-table value of 1.984, and the significance level of 0.198 exceeds the standard threshold of 0.05. Factors hindering communication between parents and children in the Perdana Kusuma environment include differing perceptions of specific events or situations, a significant age gap leading to a lack of understanding of contemporary child behavior by parents, and children struggling to adapt to their parents' traditional mindset and unstable emotional conditions. The anticipated outcome of this research is to provide a deeper understanding of the significance of family communication in shaping children's behavior, particularly in a military family setting. The findings aspire to contribute to the enhancement of more effective communication patterns between parents and children, fostering the development of positive and healthy behaviors among children in the Halim Perdana Kusuma environment.